Research on Overlapping Communities in Scientific Cooperation Network. Issue 1 (1st June 2022) - Wu, Fan; Yang, Can; Zheng, Xue; Li, Dongsheng; Chen, Kebin
Abstract: Science of science provides quantitative means for scientific research activities and can reveal the basic laws of scientific research. Taking the scientist cooperation network of Condensed matter physics, General relativity quantum cosmology and High energy physics phenomenology as the research object, the overlapping community structure in the network is detected by using the label propagation algorithm based on seed diffusion. Through community analysis, it is found that when the scale of scientists' cooperative network increases, the increase in the number of communities is not obvious, but the scale of each community will increase, and the probability of scientists belonging to overlapping communities will decrease. This shows that the increase in the number of authoritative scientists is not obvious after the unpopular research field becomes a popular research field. In hot research fields, the division of scientists' cooperation circles is clearer, and the cooperation frequency between circles will decrease significantly.